Comparative efficacy of Lamivudine and emtricitabine: a systematic review and meta-analysis of randomized trials. - Nathan Ford; Zara Shubber; Andrew Hill; Marco Vitoria; Meg Doherty; Edward J Mills; Andy Gray (PLoS ONE)
Introduction Lamivudine and emtricitabine are considered equivalent by several guidelines, but evidence of comparable efficacy is conflicting. Methods We searched two databases up to June 30 2013 to identify randomized and quasi-randomized trials in which lamivudine and emtricitabine were used as part of combination antiretroviral therapy for treatment-naïve or experienced HIV-positive adult patients. We only included trials where partner drugs in the regimen were identical or could be considered to be comparable. We allowed for comparisons between tenofovir and abacavir provided the study population did not begin treatment with a viral load >100,000 copies/ml. Results 12 trials contributed 15 different randomized comparisons providing data on 2251 patients receiving lamivudine and 2662 patients receiving emtricitabine. Treatment success was not significantly different in any of the 12 trials. In the three trials that directly compared lamivudine and emtricitabine, the relative risk for achieving treatment success was non-significant (RR 1.03 95%CI 0.96-1.10). For all trials combined, the pooled relative risk for treatment success was not significantly different (RR 1.00, 95%CI 0.97-1.02). No heterogeneity was observed (I (2) = 0). Similarly, there was no difference in the pooled relative risk for treatment failure (RR 1.08, 95%CI 0.94-1.22, I (2) = 3.4%). Conclusions The findings of this systematic review suggest that lamivudine and emtricitabine are clinically equivalent.